Quantitative assessment of hydrological alteration over multiple periods caused by human activities at the Jingjiang Three Outlets, China - Hongxiang Wang; Yongwei Zhu; Yaoguang Jin; Wenxian Guo (Water Supply, 2022)
The Jingjang Three Outlets (JTO) play a major role in the water-sediment transport from the Yangtze River to Dongting Lake. The hydrological regimes at the JTO (Songzi, Taiping, and Ouchi) had been changed due to the Jingjiang Cutoffs (JC), the Gezhou Dam (GD), and the Three Gorges Dam (TGD). Based on hydrological data from 1955 to 2019, the variation trend in annual streamflow was detected using three techniques, and the hydrological alteration was assessed with the Range of Variability Approach. Conclusions are as follows: (1) the inflection points consistent with human activities and the time series were divided into periods of P1 (1955–1971), P2 (1972–1985), P3 (1986–2002), and P4 (2003–2019); (2) human activities made a greater contribution to streamflow change than climate change; (3) the hydrological alteration degree caused by the JC, GD, and TGD projects were 56%, 47%, and 52% at the Songzi outlet; 57%, 41%, and 57% at the Taiping outlet; and 57%, 41%, and 57% at the Ouchi outlet; and (4) the ability of division from the Yangtze River to Dongting Lake is weakening and the hydrological regimes at the JTO are deteriorating due to the JC, GD, and TGD, resulting in negative impacts on the biotic composition, structure, and function of riparian ecosystems. This study provides useful insight for ecosystem protection under hydrological alteration. HIGHLIGHTS Quantitative assessment of hydrological alteration over multiple periods.; Differentiated the influence of cutoffs projects and dam construction on hydrological alteration.; Discussed the negative impacts of hydrological alteration on ecosystems and the countermeasures for future.;